IMPLEMENTATION EXEMPLARY AND HABITUATION METHODS IN IMPROVING CHARACTER - Jaenal Abidin; Syaiful Anwar; Imam Syafe’i (Sean Institute, 2023)
Education as a process of learning activities to gain character values. Implementation of character requires continuous time so it requires school readiness and the right method to implement it. This study aims to evaluate the implementation of exemplary and habituation methods in improving the character of students in learning Islamic religious education. The method used is qualitative using descriptive analysis. The sampling technique used was purposive sampling for teachers, vice curricula and principals, simple random sampling for students. Data collection techniques with observation, interviews, and documentation. Implementation of exemplary and habitual methods in terms of planning RPP, Prota, and Promes. The implementation stage of the educator exemplifies the Duha prayer, congregational prayer, reading short surahs before class, dressing modestly according to the rules, greeting, shaking hands with the teacher, praying before and after starting learning, 5S behavior (greeting, greetings, smiles, good manners), arrives on time, reads the Al-Qur’an by getting used to memorizing, makes it a habit to AWAS, LIBRA, saves trash, ant operations, and Friday donations. The visible characters are religious, responsible, polite, disciplined, care for the environment, and care for the social, but need to be strengthened at the planning stage by incorporating the implementation of character values ​​and assessment sheets in the lesson plans that are made.